Commitment to Work: Assessing Heterogeneity in the Work-Crime Relationship from a Social Control Perspective - Jaynes, Chae M. (Journal of developmental and life-course criminology, 2022)
Research evaluating the employment-crime relationship has paid little attention to individuals’ behavior at work, despite the strong conviction that commitment to work should reduce offending. This study evaluates the relationship between job commitment and offending, and examines the role of job quality in the relationship. Hybrid fixed effects models are applied among a sample of high-risk adults. Findings suggest that transitioning from not working to working in a job that one has low commitment to can be criminogenic. In addition, increased commitment is associated with a reduced likelihood of offending. There is no significant evidence that the association between job commitment and offending is mediated or moderated by changes in job quality. Results also indicate “red flag” work behaviors associated with offending. These findings highlight the importance of job commitment in evaluating the work-crime relationship and caution criminologists against making assumptions about the role of job quality.